1992
DOI: 10.1007/bf01987884
|View full text |Cite
|
Sign up to set email alerts
|

Actions and cross-reactivity of antiallergic agents and a calcium channel antagonist on rat peritoneal mast cells. Difference in the action mechanisms and cross-reactivity among the agents

Abstract: The actions of the antiallergic agents, disodium chromoglycate (DSCG), tranilast and ketotifen, and of a calcium channel antagonist, nicardipine, and cross-reactivity among the agents were examined by observing the inhibition of 45Ca uptake and histamine release in rat mast cells stimulated by antigen and compound 48/80 (comp. 48/80). 1) All agents inhibited 45Ca uptake and histamine release in mast cells stimulated by antigen. The inhibition of 45Ca uptake by the antiallergic agents paralleled the inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…On the other hand, we demonstrated in an in vitro study that propolis inhibited histamine release from rat mast cells induced by compound 48/80. The effect of propolis was more potent than representative anti-allergic drugs, tranilast and disodium chromoglycate [11]. These findings suggest that the inhibitory effects of propolis on scratching behavior and vascular permeability induced by compound 48/80 observed in the late phase may be due to a mast cell-dependent mechanism.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, we demonstrated in an in vitro study that propolis inhibited histamine release from rat mast cells induced by compound 48/80. The effect of propolis was more potent than representative anti-allergic drugs, tranilast and disodium chromoglycate [11]. These findings suggest that the inhibitory effects of propolis on scratching behavior and vascular permeability induced by compound 48/80 observed in the late phase may be due to a mast cell-dependent mechanism.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, activation of H 2 receptors locating on cells of gastric mucosa and big blood vessels may increase intracellular cAMP and decrease intracellular calcium levels (Hill, 1990;Tanizaki et al, 1992). Lack of inhibitory effect of ranitidine on increased gastric microvascular permeability in Salmonella typhi-infected rat stomachs is probably associated with H 2 receptors that mainly being present on the gastric vascular smooth muscle cells instead.…”
Section: Discussionmentioning
confidence: 97%
“…Ketotifen is shown to inhibit cellular [ 45 Ca] uptake and histamine biosynthesis in mast cells stimulated by antigen (Tanizaki et al, 1992). In the gastrointestinal tract, histamine may cause a potent contraction of the smooth muscle cells and gastric mucosal internal leak (Demling et al, 1982) that may contribute to plasma protein, electrolyte and water loss.…”
Section: Discussionmentioning
confidence: 98%
“…These results sug gest that ketotifen inhibits food antigen-specific prolifer ative responses of PBMCs in patients with food-sensitive AD. Tanizaki et al [9] reported that ketotifen inhibited the Ca2+ uptake into cells. Therefore, ketotifen may in hibit part of the processes ranging from antigen recog nition by T-cell receptors to Ca2+-dependent signal trans duction in T-cell responses to the food antigen.…”
Section: Discussionmentioning
confidence: 99%